PENGARUH PENERAPAN MODEL DISCOVERY LEARNING BERBANTUAN PHET SIMULATION TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN IPA DI SEKOLAH DASAR - Resa Azahra; Afridha Laily Alindra; Wina Mustikaati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Critical thinking skills are one of the essential competencies that students need to master in science education. The low level of critical thinking skills among elementary school students is the primary reason for conducting this research. This study aims to: 1) Determine the effect of implementing the Discovery Learning model supported by PhET Simulation media in enhancing the critical thinking skills of elementary school students; 2) Assess whether the improvement in critical thinking skills of students using the Discovery Learning model with PhET Simulation media is better compared to those receiving scientific learning. The method used in this research is a quasi-experimental design with a non-equivalent pretest-posttest control group, involving 54 students on the topic of electrical energy. The instrument used to collect data before and after the learning process is a critical thinking skills test. The results of the study indicate that: 1) There is an effect of learning using the Discovery Learning model supported by PhET Simulation media on students' critical thinking skills; 2) The improvement in critical thinking skills of students who participated in the Discovery Learning model is better than that of students who received scientific learning. Since this research focuses on critical thinking skills in the aspect of competence, it is recommended for future studies to explore critical thinking skills in other aspects, such as knowledge. Keywords: discovery learning model, phet simulation, critical thinking skills